51.7k views
14 votes
What is the answer?

plz help

What is the answer? plz help-example-1
User SyAu
by
6.1k points

2 Answers

11 votes

Answers:

  • The simplified expression is -4x
  • The value is -516

===========================================

Explanation:

To simplify this, we combine the coefficients. This works because all of the terms have 'x' in them and nothing else (they are all like terms). We can think of this problem as trying to evaluate -12+14-6. This simplifies to -4

So -12x+14x-6x simplifies to -4x

Afterward, we replace x with 129 to get

-4x = -4*129 = -516

User Dave Hunt
by
5.5k points
2 votes

Answer:-516

Explanation:

User Pbhle
by
5.6k points